2018
DOI: 10.1021/acs.jpca.7b10781
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Investigation into Rate-Determining Factors in Electrophilic Aromatic Halogenation

Abstract: The halogenation of monosubstituted benzenes in aqueous solvent was studied using density functional theory at the PCM-M06-2 X/6-311G(d,p) level. The reaction with Cl begins with the formation of C atom coordinated π-complex and is followed by the formation of the σ-complex, which is rate-determining. The final part proceeds via the abstraction of the proton by a water molecule or a weak base. We evaluated the use of the σ-complex as a model for the rate-determining transition state (TS) and found that this mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 44 publications
1
40
0
Order By: Relevance
“…A comparison of the C−N distance in π‐complex, TS1, and σ‐complex shows that TS1 has a structure more similar to π‐complex. Thus, according to the Hammond postulate the direct amination has an earlier transition state than halogenations since halogenations show a closer structural similarity between the σ‐complex and corresponding transition state …”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…A comparison of the C−N distance in π‐complex, TS1, and σ‐complex shows that TS1 has a structure more similar to π‐complex. Thus, according to the Hammond postulate the direct amination has an earlier transition state than halogenations since halogenations show a closer structural similarity between the σ‐complex and corresponding transition state …”
Section: Resultsmentioning
confidence: 92%
“…The predicted ρ values and observed similarities allowed us to put amination of arenes by H 2 N 3 + somewhere close to nitration (Table ). As we stated above, amination is characterized by an earlier transition state than halogenations since TS1 in amination shows more similarity to the π‐complex, whereas TS in halogenations is more similar to the σ‐complex ,. Nitration was also shown to have an earlier transition state than halogenations .…”
Section: Resultsmentioning
confidence: 99%
“…In 2018, they reported a theoretical investigation on the halogenation of mono‐substituted benzenes using Density Functional Theory (DFT) at PCM−M06‐2X/6‐311G(d,p) level. It was found that the reactions with Cl 2 and Br 2 procced by a stepwise mechanism, while the iodination with ICl involves a concerted mechanism …”
Section: Introductionmentioning
confidence: 99%
“…A more realistic mechanism can rationalize some of these observations by the formation of a π-complex, which can sometimes be rate-limiting but not selectivity-determining (Scheme ). , Furthermore, for some electrophiles such as iodine, the σ-complex may not be a true intermediate, but rather a transition state with a concerted deprotonation, detectable by a significant kinetic isotope effect . However, brominations and chlorinations seem to be reasonably well approximated by the schoolbook mechanism.…”
Section: Introductionmentioning
confidence: 99%